Fundamentals of plasma physics - Bellan, Paul Murray, 1948- (Cambridge University Press, 2006)
This rigorous explanation of plasmas is relevant to diverse plasma applications. More thorough than previous texts, it exploits new powerful techniques to develop deeper insights into plasma behavior. Written for advanced students, it explores a host of essential and advanced topics while emphasizing the fundamentals that apply to all plasmas.